External flows and inclusive human development in Sub-Saharan Africa - Simplice Asongu; Ivo J. Leke (African Governance and Development Institute (AGDI), 2017)
The study assesses how external flows influence inclusive human development in a panel of 48 countries in Sub-Saharan Africa for the period 2000-2012. The empirical evidence is based on Tobit regressions and Generalised Method of Moments. The findings from both estimation techniques reveal that remittances and FDI increase inclusive development whereas foreign aid has the opposite effect. The results suggest some positive and negative impacts of interest for further analysis. First, remittances are negatively associated with: (i) Middle income countries compared to Low income countries where the effect is not significant; (ii) French Civil law countries compared to English Common law countries where the effect is positive and (iii) Resource-rich countries compared to their Resource-poor counterparts where the effect is positive. Second, foreign aid is more negatively linked to Low income, French Civil law, Islam-dominated, Un-landlocked, Resource-rich and Politically-unstable countries. Third, FDI is positively associated with: (i) Low income, French Civil law and Landlocked countries compared to respectively Middle income, English Common law and Un-landlocked countries where the effect is insignificant and (ii) Politically-stable countries compared to their Politically-unstable counterparts where the effect is negative.
Keywords: F21; F24; F35; I30; O55; 330; Foreign investment; Remittances; Foreign aid; Inclusive development; Africa